أهمية تطبيق الاتجاهات الحديثة للتعليم والتأهيل المحاسبي وفق معايير التعليم المحاسبي الدولية في تعزيز جودة المخرجات المحاسبية: دراسة حالة الجزائر - تونس - المغرب - بن صالح، عبدالله سليمان; راتول، محمد (جامعة عمار ثليجي الأغواط - كلية العلوم الاقتصادية والتجارية وعلوم التسيير, 2016)
ترتكز هذه الدراسة على أهمية تطبيق معايير التعليم المحاسبي الدولية في تحسين جودة التعليم المحاسبي في الجامعات من خلال دراسة حالة الجزائر، تونس والمغرب، وتهدف إلى اقتراح كيفية تطبيقها في تحسين جودة المقررات المحاسبية في الجامعات من خلال تحليل ودراسة محتوى معايير التعليم المحاسبي الدولية وإمكانية تطبيقها لتحسين محتوى المقررات المحاسبية الجامعية.
This research is based on a proposed conception of application of standards accounting education and its role in quality control of accounting curricula in Algeria, Tunisia and morocco. The rationale behind the study was the in adherence to international standards when designing accounting courses at universities, which fact that negatively affects the quality of accounting and is reflected in neglect of training aspects during study. Hence, this research aims to shed light on international education accounting and how it can be utilized when designing accounting courses within universities. The secondary goals include study and analysis of standards of accounting education and how they can be made use of in designing accounting courses, as well as drawing a framework that can guide in designing and evaluating these courses.
Keywords: التأهيل المحاسبي -- المعايير المحاسبية -- طلبة الجامعات